A nonfullerene acceptor utilizing a novel asymmetric multifused-ring core unit for highly efficient organic solar cells. Issue 18 (30th April 2018) - Li, Chao; Xie, Yuanpeng; Fan, Bingbing; Han, Guangchao; Yi, Yuanping; Sun, Yanming
Abstract : In this communication, a novel asymmetric ladder-type thiophene-phenylene-thieno[3, 2- b ]thiophene-fused building block TPTT and the corresponding asymmetric nonfullerene acceptor TPTT-IC were reported for the first time. Abstract : In this communication, a novel asymmetric ladder-type thiophene-phenylene-thieno[3, 2- b ]thiophene-fused building block TPTT and the corresponding asymmetric nonfullerene acceptor TPTT-IC were reported for the first time. Organic solar cells (OSCs) fabricated with a wide-bandgap polymer PBT1-C as the donor and TPTT-IC as the acceptor yielded a high power conversion efficiency (PCE) of 10.5% with an open-circuit voltage ( V oc ) of 0.96 V, a short-circuit current ( J sc ) of 15.6 mA cm −2 and a fill factor (FF) of 70%, which is the highest PCE value reported in the literature so far for OSCs based on asymmetric nonfullerene acceptor materials.